A Conceptual Framework for Rescheduling Elective Pediatric Gastroenterology Procedures Following COVID-19 Pandemic Lockdown. (September 2020) - Kaur, Panamdeep; Attard, Thomas M.; Fishman, Douglas S.; Zapata, Fernando; Ditsch, Donna; Thomson, Mike; Schurman, Jennifer V.
Abstract : Elective surgical and endoscopic procedures were suspended nationwide during the March 2020 COVID-19 pandemic to minimize exposure and healthcare resource utilization. This resulted in an unprecedented backlog of procedures in most clinical practices including pediatrics. Our group developed an internal process toward the rational development of an algorithm prioritizing elective procedures. This was based on patient disease severity defined by the presence of alert symptoms, symptom severity for dysphagia and abdominal pain, and diagnostic investigation findings. The underlying rationale is to prioritize patients in whom suspected disease course would be greatest impacted by endoscopy. We developed a nurse phone call-based process utilizing REDCap®, identifying relevant symptoms categorized by severity, and a validated functional impairment questionnaire for abdominal pain. We abstracted key laboratory and radiological findings also categorized by severity. The order of priority of procedures was established on the basis of a 4-tiered system factoring both presence and severity of symptoms or prior diagnostic testing results. We present the framework that we have adopted toward prioritizing procedures with the assumption that it offers an objective methodology and that can be efficiently and more broadly applied to other similar practice scenarios. Our tool may have wide-ranging implications both in the current COVID-19 pandemic and in other scenarios of limited resource allocation and deserves further investigation.